A drain- and catheter-free enhanced recovery protocol to achieve discharge within 23 hours of laparoscopic pyeloplasty surgery: Is this feasible and safe?. (July 2016) - Donati-Bourne, Jack; Husaini, Muhammad Idzwan; Pillai, Praveen; Mathias, Suresh Jay; Fernando, Herman; Luscombe, Christopher; Golash, Anurag
Objective: The objective of this article is to review the outcomes of our updated single-centre extended experience of an innovative enhanced recovery pathway to perform catheter- and drain-free laparoscopic pyeloplasties, achieving safe discharge within 23 hours of surgery. Patients and methods: We conducted a retrospective review of patients who underwent a standard trans-peritoneal laparoscopic pyeloplasty repair over an antegrade stent in our centre by a single surgeon, between 1 September 2007 and 1 February 2015. Patients who had a urinary catheter and/or peri-nephric drain inserted intraoperatively and were not planned for day-case discharge were excluded. Data were collected for duration of in-patient stay, readmission rates and reasons for these. Successful outcome was deemed both in subjective improvement of patient symptoms and/or objective improvement in post-operative MAG-3 renogram curve. Results: Fifty-eight patients were included. A total of 74% ( n = 43) were successfully discharged as day-case, and four of these were readmitted. Fifteen patients required in-patient stay, of whom two were readmitted. Successful outcome was recorded in 93% ( n = 54). Conclusion: The insertion of a drain and catheter are not essential in laparoscopic pyeloplasty. Avoidance of unnecessary tubes facilitates day-case surgery with no adverse effect on outcome. At our institute all patients are now offered the enhanced recovery protocol for laparoscopic pyeloplasty with resulting benefits both to patients and the local health economy.